Relationships among drinking and smoking habits, history of diseases, body mass index and idiopathic sudden sensorineural hearing loss in Japanese patients. (10th March 2017) - Umesawa, Mitsumasa; Kobashi, Gen; Kitoh, Ryoshuke; Nishio, Shin-ya; Ogawa, Kaoru; Hato, Naohito; Sone, Michihiko; Fukuda, Satoshi; Hara, Akira; Ikezono, Tetsuo; Ishikawa, Kotaro; Iwasaki, Satoshi; et al.
Abstract: Objectives: To present the cardiovascular risk factors in idiopathic sudden sensorineural hearing loss (SSNHL) patients enrolled in a nationwide epidemiological survey of hearing disorders in Japan. Materials and methods: We compiled the cardiovascular risk factors in 3073 idiopathic SSNHL subjects (1621 men and 1452 women) and compared their proportions with controls as part of the National Health and Nutrition Survey in Japan, 2014. The cardiovascular risk factors consisted of drinking and smoking habits, a history of five conditions related to cardiovascular disease and body mass index. Results: The proportion of current smokers was significantly higher among men aged 50–59, 60–69 and 70+ and among women aged 30–39, 40–49 and 60–69. The proportion of patients with a history of diabetes mellitus was significantly higher among men aged 50–59, 60–69 and 70+, but not in women. In addition, male and female SSNHL subjects aged 60–69 showed lower proportions of current drinking; and female SSNHL subjects aged 60–69 showed higher proportions of overweight (BMI ≥25 kg/m 2 ). Conclusions: The present cross-sectional study revealed showed significantly higher proportions of current smokers among both men and women as well as those with a history of diabetes mellitus among men across many age groups in patients with idiopathic SSNHL compared with the controls.